Nodule growth and nitrogen fixation of Calopogonium mucunoides L. show low sensitivity to nitrate - Camargos, Liliane S. [UNESP]; Sodek, Ladaslav (Springer Nature, 2010)
It is well established that nitrate is a potent inhibitor of nodulation and nitrogen fixation in legumes. The objective of this study was to demonstrate the relative insensitivity of these processes to nitrate with Calopogonium mucunoides, a tropical South American perennial legume, native to the cerrado (savannah) region. It was found that nodule number was reduced by about half in the presence of high levels of nitrate (15 mM) but nodule growth (total nodule mass per plant) and nitrogen fixation (acetylene reduction activity and xylem sap ureide levels) were not affected. Other sources of N (ammonium and urea) were also without effect at these concentrations. At even higher concentrations (30 mM), nitrate did promote significant inhibition (ca. 50%) of acetylene reduction activity, but no significant reduction in xylem sap ureides was found. The extraordinary insensitivity of nodulation and N2 fixation of C. mucunoides to nitrate suggests that this species should be useful in studies aimed at elucidating the mechanisms of nitrate inhibition of these processes. © 2010 Springer Science+Business Media B.V.
Keywords: Calopogonium mucunoides; N2 fixation; Nitrate; Nodulation; acetylene; ammonium; concentration (composition); growth rate; inhibition; inhibitor; legume; nitrate; nitrogen fixation; nodulation; perennial plant; sensitivity analysis; urea; Georgia; Savannah; United States; Desmodium